Mobility for learners and staff - higher education students and staff mobility - inter-institutional agreement mobility 2017-2021 between programme countries - Sapienza Università di Roma and Universidade Lusíada de Lisboa - Universidade Lusíada (2018)
- Cooperate for exchange of students and/or staff in the context of the Erasmus+ programme; - Erasmus subject area: management and administration.